Significant changes to the international building code 2021 - Thornburg, Douglas W.; Hyde, Sandra; Woodward, Jay (McGraw-Hill, 2021)
Gain full access to over 155 of the most significant changes to the International Building Code, including the real-world application of those changes and how they originated ? all in a single, easy-to-use resource. SIGNIFICANT CHANGES TO THE INTERNATIONAL BUILDING CODE 2021 Edition provides a comprehensive analysis of significant changes since the 2018 IBC , offering key insights into its contents and implications. Coverage includes changes made to both structural and non-structural provisions. Each change analysis features the affected code sections and identifies the change with strikethroughs and underlines to show modifications to the existing language. Each change is accompanied by a quick summary, detailed illustrations, and discussion of its significance, which brings the technical jargon of the code to life in a real-world setting. The attention to detail, logical organization, and thorough yet concise coverage found in this resource make it an ideal tool for transitioning from the 2018 IBC.